2021
DOI: 10.1016/j.toxrep.2021.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Co-exposure of sodium arsenite and uranyl acetate differentially alters gene expression in CD3/CD28 activated CD4+ T-cells

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Zeng et al reported differential methylation of 125 CpGs mapped to 79 genes in the e-waste-exposed group with higher concentrations of Pb, Cd, Mn and Cr in neonatal umbilical cord blood [ 32 ]. These genes are involved in signaling pathways related to NF-κB activation, adherens junction, TGF beta and apoptosis [ 33 ]. Another study showed that prenatal exposure to 12 metals (As, Cd, Cr, Cs, Cu, Hg, Mg, Mn, Se and Zn) associated with DMPs located in genes associated with the regulation of NF-κB signaling as well as several biological processes such are neurodevelopment, inflammatory response, cellular response to stress and DNA damage and apoptosis [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Zeng et al reported differential methylation of 125 CpGs mapped to 79 genes in the e-waste-exposed group with higher concentrations of Pb, Cd, Mn and Cr in neonatal umbilical cord blood [ 32 ]. These genes are involved in signaling pathways related to NF-κB activation, adherens junction, TGF beta and apoptosis [ 33 ]. Another study showed that prenatal exposure to 12 metals (As, Cd, Cr, Cs, Cu, Hg, Mg, Mn, Se and Zn) associated with DMPs located in genes associated with the regulation of NF-κB signaling as well as several biological processes such are neurodevelopment, inflammatory response, cellular response to stress and DNA damage and apoptosis [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the CpGs differentially methylated in response to specific metals, the authors reported DMPs annotated to genes in human leukocyte antigen (HLA) region overlapping for Cr, Cs, Cu, Hg, Mg and Mn metals [ 13 ]. Importantly, the toxicological impact of metals is relevant to mixtures and concentrations they co-exist in the environment [ 33 ]. The study found that in T-cell culture, arsenic exposure only vs exposure to arsenic and uranium mixture activates different signaling pathways, including NF-κB activation in response to arsenic and uranium co-exposure [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Tnf, a tumor necrosis factor, plays a role in inflammation induction and can impact the expression of Ccl2, Ccl5 and Il6, thereby intensifying the inflammatory response [87], as illustrated in Figure 9A. Similarly, Il6 can modulate Hmox1 expression in response to oxidative stress and influence TBX21 activation in Th17 T cells [88]. On the other hand, CCL2 and CCL5 participate in the recruitment of inflammatory cells [89] and can be regulated by Il6, Tnf and other inflammatory mediators.…”
Section: The Assessment Of the L-929 Cell Line After Exposure To The ...mentioning
confidence: 99%